Anti-diarrheal, Analgesic and Anti-microbial activities of the plant Lalmesta (Hibiscus sabdariffa): A review (International Journal of Pharmaceutical and Life Sciences, 2012)
The aim of this study was to phytochemically investigate the ethanolic extract of Hibiscus sabdariffa Linn. calyces and to evaluate the analgesic, anti-microbial and anti-diarrheal activities of this. The calyces of Hibiscus sabdariffa were separated from the other plant parts and sun dried and extracted using ethanol and phytochemically and pharmacologically evaluated.Different Phytochemical tests were performed for phytochemical screening and for determining the functional groups. Different methods like Disc diffusion method for antimicrobial activity determination, Castor oil induced diarrhea in mice method for the antidiarrheal study and Acetic acid induced writhing test for analgesic activity were employed. Phytochemical screening of the calyces of Hibiscus sabdariffa ensured the presence of alkaloid, flavonoids, saponins, tannins in the crude ethanolic extract. The peripheral analgesic activity was evaluated by acetic acid induced Writhing method. The extract produced 66.85% (p< 0.001) inhibition of writhing in mice at the dose of 500-mg/kg body weight, which is comparable to diclofenac sodium (78.45% (p